Exergy analysis of laminar fluid flow in stainless steel microtubes. (2nd December 2011) - Parlak, Nezaket; Gur, Mesut; Engin, Tahsin; Kucuk, Hasan
In the study, exergy analysis of steady laminar fluid flow in stainless steel microtubes with diameters between 103 ?m and 179 ?m were conducted in the adiabatic conditions experimentally. The exergy losses were obtained for deionised water flowing in rough microtubes with the surface relative roughness of 2?6%. Results indicated that the exergy loss was in a good agreement with the conventional theory and the increasing in relative roughness leads to increasing exergy loss. As Re increases, measured exergy losses were found to be significantly higher than that of the predicted values.